2-(3-tolyl-3-methylcyclobutyl)-2-hydroxyethyl and 2-(3-tolyl-3-methylcyclobutyl)-2-ketoethyl methacrylates: synthesis, polymerization, and characterization by spectroscopic and thermal analysis - Demirelli, K; Coskun, M; Degirmenci, M (Vsp Bv, 1999)
Two new methacrylate monomers with a hydroxyl or keto-bearing side-chain, including cyclobutane and tolyl rings - 2-(3-tolyl-3-methylcyclobutyl)-2-hydroxyethyl methacrylate (TCHEMA) and 2-(3-tolyl-3-methylcyclobutyl)-2-ketoethyl methacrylate (TCKEMA) - were first synthesized and then characterized by FT-IR, H-1-NMR, and C-13-NMR. Radical polymerization of both monomers were carried out with benzoyl peroxide as an initiator in 1,4-dioxane at 60 degrees C. FT-IR, H-1-NMR, and C-13-NMR techniques were used in the identification of both polymers. They were also characterized by GPC and thermal analysis. The oxime and hydrazone derivatives of poly(TCKEMA) were also prepared and characterized by FT-IR, TGA, and DSC techniques.
Keywords: cyclobutane ring; 2-hydroxyethyl methacrylate; hydrazone; oxime